Developing a blog trust scale via an international Delphi panel - Juan Sánchez-Villar; J. Enrique Bigné Alca\~niz (European Research on Management and Business Economics (ERMBE), 2020)
Although trust is one of the most widespread and studied constructs in marketing and management, its definition, versatility and different application areas may have fostered a certain dispersion when measuring this concept. Despite the increasing importance of blogs, specific scales for, and measures of, trust have not been considered in the literature. This paper proposes a scale to measure online trust in the blog domain (Blog Trust Scale, BTS) through the development of an international Delphi panel consisting of 14 experts from 5 different countries. As a result, we have developed a solid measurement instrument of online trust in blogs, composed of 12 items and tested in four different countries.
Keywords: M10; 650; Blog; Delphi panel; Online trust; Scale; Trust